2022
DOI: 10.3389/fendo.2022.948176
|View full text |Cite
|
Sign up to set email alerts
|

Growth differentiation factor-15 as a modulator of bone and muscle metabolism

Abstract: This study aims to clarify the potential role of growth differentiation factor-15 (GDF-15) as a myokine in bone metabolism and muscle function in females with osteoporosis. In total, 45 female participants (71.0 ± 8.5 years) with distal radius fractures were recruited. Participants were classified as healthy/osteopenic (n = 28) (CON) or osteoporotic (n = 17) (OP) according to their T-score from the areal bone mineral density (aBMD) of the femoral neck. Body mass index, upper arm and calf circumferences, and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…In contrast, another study in young men did not show any association between RBP4 and BMD (50). Furthermore, serum GDF15 level, which may affect bone metabolism or muscle homeostasis in old women via inflammatory responses (51), seemed to have positive linear correlation with the presence of LRH in the current study. Further research is essential to understand the role of RBP4 and GDF15 levels on musculoskeletal health in the older adults with LRH.…”
Section: Discussionsupporting
confidence: 53%
“…In contrast, another study in young men did not show any association between RBP4 and BMD (50). Furthermore, serum GDF15 level, which may affect bone metabolism or muscle homeostasis in old women via inflammatory responses (51), seemed to have positive linear correlation with the presence of LRH in the current study. Further research is essential to understand the role of RBP4 and GDF15 levels on musculoskeletal health in the older adults with LRH.…”
Section: Discussionsupporting
confidence: 53%
“…GDF15 has been proved to be a new biomarker for the diagnosis, progression or prognosis of the above diseases and become a new target for the development of drugs [17][18][19][20]46,47 . Previous study showed that, GDF15 is a myokine in bone metabolism and muscle function in females with osteoporosis 23,48 . However, the role of GDF15 on LBP has not been demonstrated.…”
Section: Discussionmentioning
confidence: 95%
“…The pro-inflammatory cytokines including interleukin-6, TNF-α, and interleukin-1β on pathogenesis of sarcopenia and osteoporosis have been demonstrated previously ( 29–32 ). Among them, IL-6 and TNF-α appear to play a part in preserving muscle–bone homeostasis as myokines ( 18 , 33 ). Hence, the results from RNA sequencing data validated the importance of inflammatory response in molecular background muscle–bone interaction, as suggested in previous reports.…”
Section: Discussionmentioning
confidence: 99%